Three QTL from Oryza meridionalis Could Improve Panicle Architecture in Asian Cultivated Rice - Ying Yang; Yu Zhang; Jing Li; Peng Xu; Zhijuan Wu; Xianneng Deng; Qiuhong Pu; Yonggang Lv; Walid Hassan Ali Soliman Elgamal; Sheikh Maniruzzaman; Wei Deng; Jiawu Zhou; et al. (Rice, 2023)
Abstract Rice panicle architecture is directly associated with grain yield and is also the key target in high-yield rice breeding program. In this study, three BC6F2 segregation populations derived from the crosses between two accessions of Oryza meridionalis and a O. sativa spp. japonica cultivar Dianjingyou 1, were employed to map QTL for panicle architecture. Three QTL, EP4.2, DEP7 and DEP8 were identified and validated using substitution mapping strategy on chromosome 4, 9 and 8, respectively. The three QTL showed pleiotropic phenotype on panicle length (PL), grain number per panicle (GNPP), number of primary branches (NPB), number of secondary branches (NSB), and grain width. DEP7 and DEP8 showed yield-enhancing potential by increasing GNPP, NPB and NSB, while EP4.2 exhibited wide grain, short stalk and panicle which can improve plant and panicle architecture, too. Moreover, epistatic interaction for PL was detected between EP4.2 and DEP7, and epistatic analysis between DEP7 and DEP8 for GNPP and NPB also revealed significant two QTL interactions. The result would help us understand the molecular basis of panicle architecture and lay the foundation for using these three QTL in rice breeding.